The role of Phetchaburi Rajabhat University in the revitalization of Tharaengok community's Nasep music - Chantanapumma, Jakrin; Laovanich, Monsikarn (Journal of Humanities and Social Sciences Review, 2024)
At present, studying and gathering of cultural knowledge in the community area more prevalent especially local higher education institutions which focuses on collecting knowledge and strengthening the community according to the academic service mission. One of the important missions of Phetchaburi Rajabhat University is to encourage communities to be strong and generate sustainable income. Therefore, there is a promotion of research on Nasep music of the Muslim group of Tharaengok Subdistrict in order to lead.There was a concrete preservation of nasep music of the community through the following processes: 1) Knowledge collection 2) Integration of learning management with the community 3) Continuous promotion of activities from government and private agencies 4) Encouraging communities to see the value of what they have and 5) Support for the expansion of the body of knowledge to develop as a source of learning. All of these processes are important in promoting the concept of building a strong community, realize the importance of what you have, and extending the body of knowledge to bring value to the community in a sustainable manner.